2010
DOI: 10.1177/1753193410377845
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Splinting or Conservative Treatment for Displaced Fractures of the Little Finger Metacarpal Neck? a Prospective Study

Abstract: Forty patients with a 30° to 70° palmar displacement of a little finger metacarpal neck fracture were treated either with closed reduction and intramedullary splinting, or conservatively without reduction. Functional mobilization was started after 1 week in both groups. A radiological and clinical assessment of flexion and extension of the small finger metacarpophalangeal joint was done at 2 and 6 weeks, and at 3, 6 and 12 months. In addition patient satisfaction and grip strength were recorded at 12 months. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 19 publications
2
61
0
3
Order By: Relevance
“…It included 69 juvenile patients who received surgery intervention due to fifth metacarpal neck fractures in the Department of Pediatric orthopaedics, Shanghai Children's Medical Center affiliated to Medicine School of Shanghai Jiaotong University (Shanghai, China) between February 2012 and January 2014. The inclusion criteria were as follows: i) volar angulation of the fifth metacarpal head >30˚ (8) or ii) rotational deformity (>15˚) (13). Participants were excluded if they had segmental comminuted fractures or intraarticular involvement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It included 69 juvenile patients who received surgery intervention due to fifth metacarpal neck fractures in the Department of Pediatric orthopaedics, Shanghai Children's Medical Center affiliated to Medicine School of Shanghai Jiaotong University (Shanghai, China) between February 2012 and January 2014. The inclusion criteria were as follows: i) volar angulation of the fifth metacarpal head >30˚ (8) or ii) rotational deformity (>15˚) (13). Participants were excluded if they had segmental comminuted fractures or intraarticular involvement.…”
Section: Methodsmentioning
confidence: 99%
“…However, complications including marked angulation accompanied by potential reduction in the range of motion (ROM) and reduced grip strength (10,11) may occur. Previous studies have demonstrated that antegrade intramedullary nailing (AIMN) is a reliable and minimally invasive method to treat metacarpal fractures (12)(13)(14). Although AIMN was reported to be a safe and reliable option to treat 66 children and juveniles with metacarpal fractures (15), more cases and studies are required to provide clinical guidance for treating the disease in juvenile patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of these fractures can be treated nonoperatively, surgery may be indicated when there is shortening of the metacarpus by more than 3 mm or when severe apex-dorsal angulation is present [4,6,16,[18][19][20][21]. It remains controversial how much angulation can be tolerated without loss of hand function or hand pain [18]. A biomechanical study showed a fracture angle up to 30°is compatible with near-normal mechanics, but a fracture angle greater than 45°produces significant muscle shortening that can limit motion of the fifth digit [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several surgical techniques have been used to treat displaced fifth metacarpal neck fractures, including antegrade intramedullary K-wire, retrograde intramedullary K-wire, retrograde cross pinning with K-wire, transverse pinning with K-wire, external fixation, intraosseous wiring, and plate fixation [4,6,16,[18][19][20][21]. Since Foucher et al [5] described the antegrade intramedullary K-wire technique, it has been widely used and produces reliable fracture reduction and excellent ROM of the fifth finger for patients with a fifth metacarpal neck fracture [4,6,16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nicht selten kommt es zusätzlich zu einer Rotationsfehlstellung, sodass bei einer Vielzahl der Halsfrakturen der Mittelhandknochen die Indikation zur operativen Therapie gegeben ist. Hinsichtlich der palmaren Abkippung wird bei den Mittelhandknochen 4 und 5 ab einer palmaren Dislokation von 40-50°d ie operative Stabilisierung empfohlen [3,13] Eine prospektiv randomisierte Studie von Strub et al [14] zeigte, dass Patienten, bei denen eine operative Versorgung durchgeführt wurde, eine höhere Zufriedenheit und bessere ästhetische Ergebnisse aufwiesen. In einer vergleichenden Untersuchung zwischen der intramedullären Schienung und der offenen Reposition mit plattenosteosynthetischer Stabilisierung fanden sich keine signifikanten Unterschiede hinsichtlich des Disablities of the Arm, Shoulder and Hand (DASH)-Scores, des TAM ("total arc of motion") sowie der Verkürzung des betroffenen Mittelhandknochens [9].…”
Section: Subkapitale Frakturen Der Mittelhandknochenunclassified